Uso e ocupação do solo em São Paulo, alterações climáticas e os riscos ambientais contemporâneos - Jane Zilda dos Santos Ramires; Neli Aparecida de Mello-Théry (Confins)
Human interventions in nature, particularly in the last century, with intense use and degradation of environmental resources contributed for the emergence of the actual environmental crisis; that is, changes to the Earth's climate system. The theory that the increased temperature Earth would have been caused by only natural events weakened as in the international scientific community, represented by the Intergovernmental Panel on Climate Change, began to present data demonstrating that global warming is not a mistake; the phenomenon is related to human activities combined with natural variations in the climate system (IPCC, 2014). The current discussion involves the human contribution into this process, especially from the advent of the industrial revolution followed by technological innovations (Santos 1997, 2012; Leff 2007; Giddens, 2010). The 1st National Assessment Report from Brazilian Climate Change Panel confirms the results of the IPCC (2014), with more detailed data on climate changes in Brazil, pointing out that there will be changes in the coming decades in all regions of the country with increase in average temperature around 1° C to 6° C by the end of this century, compared to that recorded at the end of the twentieth century. Climate change generates risks to all mankind, but it is the local level that its effects have greater magnitude because the world population is concentrated in large urban agglomerations and due to the characteristic pattern of urbanization intense soil sealing, removal of vegetation and occupation of vulnerable areas. This phenomenon is exacerbated in major cities of less developed countries, where we see the increasing number of people living in extreme poverty surviving in areas of risk, such as hillsides and areas prone to flooding. The objective of this work is to demonstrate that extremes events from climate change has reached the São Paulo metro area, especially the remote and poorest areas of the city. From analysis of data provinient from two stations located in São Paulo (Santana and Ipiranga) we can observe that there were changes in the climate in São Paulo in recent decades, like the increase of the temperature and the number of days with precipitation > of 30mm and 50mm, in addition to decreasing relative humidity of the air. The results of this analysis showed that extreme events related to climate change, particularly with heavy and concentrated rainfall, has been occurring causing significant risks to its population, especially to the ones that are more vulnerable. Are the risks inherent in contemporary risk society that speaks Beck and Giddens, in face of which the public Power is challenged to implement appropriate medium and long term public policies.